Numerical Analysis of Integrated Fabry–Perot Interferometers Based on Four Core Fiber With a Helical Phase Microdisk - Yuhan Geng; Shengnan Wu; Sailing He (IEEE Photonics Journal)
The integrated Fabry-Perot (FP) interferometers structure based on four core fiber (FCF) and a helical phase-modulation microdisk (HPMD) structure is proposed. The HPMD is designed to generate π/2 phase difference between adjacent fiber cores at the end face of the FCF. Four extrinsic FP cavities are formed by the HPMD and another reflected mirror perpendicular to the fiber. The quadrature phase demodulation theory is derived and the FP cavities length can be directly calculated by the reflected intensity of the FCF. The crosstalk effect between the four cores is analyzed. In addition, the simulation results also show that the structure has strong anti-interference ability to temperature fluctuations, the sensitivity of phase difference and temperature is only 0.009 °/K. The results of phase demodulation show that the demodulation effect is better when the thickness of the phase disk is 765 nm, and the mean relative error is 0.58%. The influence of machining error of FCF on demodulation results is also analyzed. The phase demodulation relative error is 0.65% when the alignment mismatch is reach 100 μm.